Integrative analysis of carbon structure and carbon sink function for major crop production in China's typical agriculture regions. (20th September 2017) - She, Wei; Wu, Yao; Huang, Huang; Chen, Zhongdu; Cui, Guoxian; Zheng, Huabing; Guan, Chunyun; Chen, Fu
Abstract: Crop production not only creates economic values, but also has ecological functions. The carbon sink function of crops plays an important role in mitigating climate changes. This paper collected and analyzed the carbon cost data of staple crops in China, estimated the carbon sink and carbon source effects of farmlands, and quantitatively evaluated the carbon inputs and outputs of crop production systems. The results showed that the carbon footprints of crops in six typical agriculture regions were quite different, and the major crops production showed as carbon sinks in general. The carbon sequestration of different crops in the same region were significantly different, as well as the same crop in different regions. China's farmland ecosystem showed carbon sequestration effect: the total annual net carbon sink of three major crops, rice, wheat, and corn, was about 165.76 TgC, of which rice was the highest, accounting for 48.71%. This study also proposed the key ways for energy conservation and emission reduction of crop production in every region, and suggested the technology direction for improving carbon sink function. This study provided important basis for policy formulation and planning about the low-carbon agriculture development in China. Highlights: The major crops of six typical agricultural regions in China showed as carbon sinks. China's farmland ecosystem showed carbon sequestration effect. The carbon footprint was from plastic films for northwest crops, electricity for North China crops, and fertilizers for crops of the other four regions.